Ubiquitin specific protease 7 is a potential therapeutic target for gastric cancer - Wang, Zhi-Ru; Kang, Wen-Ting; Yu, Rui-Li (Frontiers in Oncology, 2025)
IntroductionAs a deubiquitinase, ubiquitin-specific protease 7 (USP7) plays a vital role in diverse cancers, nevertheless, its role in gastric cancer (GC), which is the fifth leading cause of death in diverse cancers worldwide, has rarely been reported.MethodsTo gain a comprehensive understanding about USP7 in the progression of GC, 287 paired GC tissues were collected and analyzed. ShRNA and small molecular inhibitor were used to investigate the impact of USP7 on cell proliferation. Additionally, xenograft proliferation was used to explore the effect of USP7 on tumor growth in animals.ResultsWe found that USP7 overexpression in GC tissues was correlated with several parameters of clinicopathology and poor disease-free survival rate. Meanwhile, the abrogation of USP7 suppressed GC cell proliferation by stabilizing p53 and promoting cell cycle arrest both in vitro and in vivo.DiscussionThese results indicate that USP7 may serve as a biomarker for predicting the outcomes of patients with GC. Therefore, USP7 could be a promising therapeutic target for GC treatment.